PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA CALL CARD DAN TRUTH AND DARE - Wise Meilan; Salastri Rohiat; Hermansyah Amir (University of Bengkulu, 2017)
This study aimed to compare the learning outcomes of students with using cooperative learning type Team Games Tournament (TGT) with media Call Card and Truth and Dare in SMA Negeri 05 Bengkulu Tengah. This research is quasy experimental with population all grade students in SMA Negeri 05 Bengkulu Tengah and the sample is X3 class as experiment class 1which implement instructional media truth and dare and X1 class as experiment class 2 which implement instructional media Call Card. Students learning outcomes in this research extend from the difference of pretest and posttest value. In the experimental class 1 average value of students learning outcomes 69,46 while the experimental class 2 at 58,21. Through a series of statistical test done hypothesis testing using t test (0,01) was obtained t =3,13 and t table =2,39. The results of data analysis showed that shere were significant differences in student learning result between the aplication of instructional media Truth and Dare with media Call Card in hydrocarbon compound material in X grade SMA Negeri 05 Bengkulu Tengah. This can be showed t test that has been done on student learning outcomes for cognitife aspect got the result that value t table < t. The obtained t = 3,133 mean while t table = 2,397.